Immune responses during an antarctic summer - Lugg, Desmond J.; Ursin, Holger; Donovan, Kevin; Konrad Muller, H.; Quinn, Dennis (Pathology, 1995)
The immune status of 29 members of the Australian National Antarctic Research Expeditions (ANARE) was investigated before, during, and after a 56 day summer voyage to Antarctica and correlated with psychological and physiological parameters. All subjects were healthy. Expedition personnel demonstrated decreased cell mediated immune responses (CMI) assessed by the CMI Multi-test; 21% were hypoergic. The major associated observation was a significant negative correlation with anxiety in Antarctica. However, perceived anxiety was greater before and after the voyage. No significant changes were found in T and B lymphocyte subsets, immunoglobulin and complement components and cutaneous blood flow, nor was there any clinical evidence of illness. Of the hormones examined only cortisol was low predeparture which may reflect increased perceived anxiety at that time. Changes in immune control mechanism were apparent as shown by reduced CMI responses and lowered tetanus antibody levels. Stress factors are postulated to induce depression of the immune response in Antarctica. The association with anxiety suggests that brain peptides or associated cytokines may have a role in mediating these immune events. Such alterations in immune status have implications for health management in isolated and extreme conditions.
Keywords: Antarktis; fysiologi; immunologi; psykologi

Light and productivity of phytoplankton in polar marine ecosystems: a physiological view - Sakshaug, Egil; Slagstad, Dag (Polar Research, 1991)
Keywords: Sørishavet; fysiologi; fytoplankton; planteplankton; polarområdene

Psychobiological Studies of Individuals in Small, Isolated Groups in the Antarctic and in Space Analogues - Ursin, Holger; Bergan, Tom; Collet, Jérôme; Endresen, Inger M.; Lugg, Desmond; Maki, Pauline; Matre, Roald; Molvær, Otto Inge; Müller, Helmut K.; Olff, Miranda; Pettersen, Roger C.; Sandal, Gro Mjeldheim; et al. (Environment and Behavior, 1991)
Mental and physical health are both at risk under conditions of prolonged remoteness from home and removal from normal social support networks. This article examines relevant data from small groups isolated in (a) Antarctic summer stations, (b) a Transantarctic traverse expedition, and (c) a spacecraft simulator capsule.
Keywords: Antarktis; forskningsstasjoner; fysiologi; immunologi; psykobiologi; psykologi

Basal metabolic rate of “tropical” man in a polar climate - Wilson, Ove (Biometeorology: Proceedings of the Second International Bioclimatological Congress Held at the Royal Society of Medicine, London, 4–10 Sept. 1960, Organized by "The International Society of Biometeorology", 1962)
Naked man in his mode of heat regulation can be regarded as a tropical or subtropical creature with a narrow zone of adaptability, and the difference in the BMR determined in the tropics and in a temperate zone for the same individuals does not seem to exceed 10 per cent. In the climatic extremes he raises his calorific output in situations of stress but does not adapt by further changing his BMR. Some native people, however, appear to have the ability to endure a moderate cold stress without increasing their heat production above normal basal values. The metabolic determinations made by the author on the Norwegian—British–Swedish Expedition during 2 years of continuous exposure to the Antarctic climate show that there is no difference in the mean level of the BMR of white man whether he lives in a temperate or a polar climate. Other studies in cold regions support this view. Evidence of acclimatization of man to cold will not be found in the basal metabolic rate. However, the author's investigations show that the polar climate in its extreme form, as it is encountered by man in the Antarctic, can impose certain seasonal variations in the BMR. This periodicity in BMR is probably not a direct effect of climate on metabolism, but is related to it by reason of the typical activity pattern which ensues in the Antarctic climate. In agreement are the seasonal changes in BMR in the Arctic reported by Russian workers. The preliminary results of Lewis and Masterton in North Greenland, on the other hand, do not indicate a consistent seasonal variation. In changing from a temperate to a tropical climate, the BMR may vary within a narrow range of about 10 per cent, decreasing in the hot environment, but not all persons will show such a change. The seasonal variation found by the author in a polar climate is almost of the same order as the change in the tropics. It may be that the alterations in BMR caused by a change to a tropical climate are due to similar influences, which, however, do not exhibit the same seasonal incidence, because of the uniformity of the climate the year around. This implies that the basal metabolism of white man is essentially the same in all climates, but varies within a narrow range, not as a direct result of climate itself or its mean temperature, but depending upon changes in the type of activity, food, exposure, muscle tone and other factors, which are imposed by a difference in climate and regimen.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Thermal and metabolic responses of men in the Antarctic to a standard cold stress - Milan, Frederick A; Elsner, Robert W; Rodahl, Kaare (Journal of Applied Physiology, 1961)
Thermal and metabolic responses of eight male subjects exposed nude for 2 hr to a standard cold stress (17 α 1.0 C air temperature) were examined in the austral fall, winter, and spring at Little America in the Antarctic. Mean body, average skin and foot temperatures increased significantly after 3 months. Neither rectal nor finger temperatures were changed over the year. Although basal metabolic rates were unchanged, there was a significant decrease in the metabolic responses to the standard cold stress after 3 months in the Antarctic. It is suggested that these changes represent physiological adaptations to chronic cold. Submitted on November 14, 1960
Keywords: Antarktis; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Endocrinological studies in the blue whale (Balaenoptera musculus L.) - Jacobsen, Alf P. (I kommisjon hos Dybwad, 1941)
Keywords: Sørishavet; anatomi; biologi; fysiologi; hvaler; pelagisk hvalfangst